ROLE OF CORPORATE SECURITIES IN CAPITAL MARKET - Otakhonova Shokhyora Khamidullakhon kizi (American Journals, 2025)
This article studies role of corporate securities in capital market. Moreover, types and forms of corporate securities, some aspects of different securities are analyzed in detail. Scientific conclusions and recommendations are presented on the basis of analyses.
Keywords: Share, bond, capital, capital market, securities, corporate securities, corporate securities operations.